Benthic food webs support the production of sympatric flatfish larvae in estuarine nursery habitat - Dias, Ester (2017)
Identifying nursery habitats is of paramount importance to define proper management and conservation strategies for flatfish species. Flatfish nursery studies usually report upon habitat occupation, but few attempted to quantify the importance of those habitats to larvae development. The reliance of two sympatric flatfish species larvae, the European flounder Platichthys flesus and the common sole Solea solea, on the estuarine food web (benthic versus pelagic), was determined through carbon and nitrogen stable isotope analysis. The organic matter sources supporting the production of P. flesus and S. solea larvae biomass originates chiefly in the benthic food web. However, these species have significantly different d13C and d15N values which suggest that they prey on organisms that use a different mixture of sources or assimilate different components from similar OM pools (or both).